2018
DOI: 10.1002/stem.2808
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cells Protect Against Hypoxia-Ischemia Brain Damage by Enhancing Autophagy Through Brain Derived Neurotrophic Factor/Mammalin Target of Rapamycin Signaling Pathway

Abstract: Hypoxic-ischemic encephalopathy (HIE) is a serious disease for neonates. However, present therapeutic strategies are not effective enough for treating HIE. Previous study showed that mesenchymal stem cells (MSCs) can exert neuroprotective effects for brain damage, but its mechanism remains elusive. Using in vitro coculture of rat cortical primary neurons and MSCs in HI conditions, we demonstrated that MSCs help increase brain derived neurotrophic factor (BDNF) and autophagy markers (LC3II and Beclin1) in the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 47 publications
1
34
0
Order By: Relevance
“…Mesenchymal stem cells (MSCs), a class of pluripotent cells, have been proved to exert anti‐apoptosis, anti‐inflammatory and immunoregulatory effects, and they are an emerging and promising resource that may protect islets from hypoxia or other damage, thereby promoting graft survival . Interestingly, a growing body of research has indicated there may be a potential link between the protective role of MSCs and autophagy . However, it is currently unknown whether the favourable effect of MSCs on protecting islets subjected to hypoxia is related to the regulation of autophagy.…”
Section: Introductionmentioning
confidence: 99%
“…Mesenchymal stem cells (MSCs), a class of pluripotent cells, have been proved to exert anti‐apoptosis, anti‐inflammatory and immunoregulatory effects, and they are an emerging and promising resource that may protect islets from hypoxia or other damage, thereby promoting graft survival . Interestingly, a growing body of research has indicated there may be a potential link between the protective role of MSCs and autophagy . However, it is currently unknown whether the favourable effect of MSCs on protecting islets subjected to hypoxia is related to the regulation of autophagy.…”
Section: Introductionmentioning
confidence: 99%
“…2 a). LDH, which is retained in the cytoplasm of viable cells with intact plasma membranes and released from cells after membrane damage, is considered an important indicator of necrosis [ 28 ]. Spectrophotometric analysis demonstrated that the LDH level was significantly increased in the medium of cells treated with H 2 O 2 , especially those treated with 800 μM H 2 O 2 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Autophagy is an intracellular degradation process and a cytoprotective response of cells in extreme environments, such as starvation, hypoxia, and physical stimulation [17]. Autophagy can be converted into the energy needs by removing metabolic substances from the body and damaged organelles.…”
Section: Discussionmentioning
confidence: 99%